Kesiapan Pengadilan Agama Jember dalam Melaksanakan UU No. 3 Tahun 2006 tentang Perubahan atas UU No. 7 Tahun 1989 tentang Peradilan Agama di Bidang Ekonomi Syariah: The Readiness of the Religious Court of Jember in Implementing Law Number 3 of 2006 Concerning the Amendment to Law Number 7 of 1989 on Religious Courts in the Field of Sharia Economic Affairs - Mahmudah Mahmudah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2008)
Legal reform through Law No. 3 of 2006 expanded the absolute authority of Religious Courts to the field of sharia economics, which was not previously regulated under Law No. 7 of 1989. This change demands institutional readiness, particularly regarding human resources and judges' understanding of sharia economic disputes. This research aims to describe the readiness of the Jember Religious Court in implementing the law. Using a qualitative approach with data collection methods of interviews, observation, and documentation, the data were analyzed descriptively and reflectively. The findings show that the Jember Religious Court is ready to implement Law No. 3 of 2006. This readiness is evidenced by the judges' participation in various training sessions and workshops on sharia business organized by the Supreme Court and the East Java High Religious Court, as well as learning from other courts that have handled similar disputes. Although no positive substantive law specifically regulates sharia economic disputes, judges utilize judicial freedom based on Law No. 4 of 2004. The main obstacle is external: the lack of willingness from sharia economic institutions to resolve their disputes at the Religious Court. It is recommended to increase socialization to sharia economic institutions and accelerate the formulation of substantive law. Pembaruan hukum melalui UU No. 3 Tahun 2006 memperluas kewenangan absolut Peradilan Agama ke bidang ekonomi syariah, yang sebelumnya tidak diatur dalam UU No. 7 Tahun 1989. Perubahan ini menuntut kesiapan institusional, khususnya dari sisi sumber daya manusia dan pemahaman hakim terhadap sengketa ekonomi syariah. Penelitian ini bertujuan untuk mendeskripsikan kesiapan Pengadilan Agama Jember dalam mengimplementasikan undang-undang tersebut. Menggunakan pendekatan kualitatif dengan metode pengumpulan data melalui wawancara, observasi, dan dokumentasi, data dianalisis secara deskriptif reflektif. Temuan penelitian menunjukkan bahwa Pengadilan Agama Jember telah siap melaksanakan UU No. 3 Tahun 2006. Kesiapan ini dibuktikan dengan partisipasi hakim dalam berbagai pelatihan dan workshop bisnis syariah yang diselenggarakan oleh Mahkamah Agung dan Pengadilan Tinggi Agama Jawa Timur, serta belajar dari pengadilan lain yang telah menangani sengketa serupa. Meskipun belum ada hukum materiil positif yang secara khusus mengatur sengketa ekonomi syariah, hakim menggunakan kebebasan kehakiman berdasarkan UU No. 4 Tahun 2004. Kendala utama bersifat eksternal, yaitu minimnya iktikad lembaga ekonomi syariah menyelesaikan sengketa di Pengadilan Agama. Disarankan peningkatan sosialisasi kepada lembaga ekonomi syariah dan percepatan penyusunan hukum materiil.